2019
DOI: 10.1177/1747493019828648
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acute ischemic stroke evaluation and the etiologic subtypes between university and nonuniversity hospitals in Isfahan, Iran

Abstract: Background and purpose Performing a proper causative workup for ischemic stroke patients is essential as it guides the direction of primary and secondary preventions. We aim to investigate the etiological evaluation of these patients in university and nonuniversity hospitals. Method We enrolled subjects from the Persian Registry of Cardiovascular Disease–stroke. Stroke patients were categorized base on an etiological-based classification (Trial of Org 10172 in Acute Stroke Treatment or TOAST) into five groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…and 21-30% lacune[55,61,62] (SupplementalTable 22). Likewise, we observed lower regional rates of SVO and lacune: in Europe, 4.1% SVO and 9.3% lacune, versus previous reports of 12-31% SVO [63-69]and 14-31% lacune;[65,[70][71][72] in the North and South America, 5.3% SVO and 9.1% lacune, versus reported SVO rates of 15-18%[55,73] and 13-18% lacune;[55,62] and in the Middle Eastern countries, 18.3% SVO and 11.3% lacune, versus 20-25% SVO[56][57][58][59][60]74] and 19-26% lacune.…”
mentioning
confidence: 45%
See 2 more Smart Citations
“…and 21-30% lacune[55,61,62] (SupplementalTable 22). Likewise, we observed lower regional rates of SVO and lacune: in Europe, 4.1% SVO and 9.3% lacune, versus previous reports of 12-31% SVO [63-69]and 14-31% lacune;[65,[70][71][72] in the North and South America, 5.3% SVO and 9.1% lacune, versus reported SVO rates of 15-18%[55,73] and 13-18% lacune;[55,62] and in the Middle Eastern countries, 18.3% SVO and 11.3% lacune, versus 20-25% SVO[56][57][58][59][60]74] and 19-26% lacune.…”
mentioning
confidence: 45%
“…[54,55] In the Middle East, our study presented 53.5% LAA, compared with the previously reported rate of 8-31%. [56][57][58][59] Small-vessel occlusion (SVO) accounted for stroke etiology in 10% of our patients, and analysis of neuro-imaging patterns showed 10.2% lacunar infarcts (lacune). These rates are lower than worldwide population-based studies-21-44% SVO, [55,60] [59,75,76] We could not identify any difference in imaging findings or subclasses of the TOAST criteria among SARS-CoV-2 infected patients who presented with chief complaints of stroke-related symptoms compared to patients with a prior diagnosis of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…1 Embolic stroke of undetermined source (ESUS) accounts for 9 to 30% of all ischemic strokes, where the exact etiology, pathophysiology, and preventable treatment of the stroke remain unknown. 1,2 Two large randomized trials, the NAVIGATE ESUS and RE-SPECT ESUS which studied rivaroxaban and dabigatran respectively, could not confirm a preventive role for direct oral anticoagulation in ESUS patients. 3,4 The ASSERT study showed an association between subclinical atrial fibrillation (AF) and an increased risk of embolic stroke and ESUS.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is one of the main causes of mortality and disability worldwide [ 1 ]. Ischemic strokes account for 87% of all strokes in the United States and 76–88% of strokes in Iran [ 2 – 7 ]. During the last decades, the incidence of ischemic strokes among young adults has been increased [ 8 ].…”
Section: Introductionmentioning
confidence: 99%